The contribution of mango fruit (Mangifera indica L.) to human nutrition and health (2023)
ABSTRACT: The mango fruit is of great economic value worldwide and of great nutritional importance. Its functional effects are due to numerous important nutrients and bioactive compounds. In this review, the benefits of mango fruit (pulp, peel, and seed) for human nutrition and health are detailed. The first part of the review presents the nutrient and phytochemical content of the mango fruit, and the second part addresses its health effects. The very diverse phytochemical components in mango fruit can be classified into several groups including macronutrients such as carbohydrates (sugars, pectin, and cellulose), proteins, lipids (X-3 and X-6 fatty acids); micronutrients such as vitamins A and C, minerals, pigments (chlorophylls, carotenoids, and anthocyanins, depending on the cultivar), phenolic compounds (phenolic acids and flavonoids), and volatile compounds. The beneficial effects of mango fruit and its components have been studied on different non-communicable diseases such as obesity, type 2 diabetes mellitus, hypertension, and cancer. A great diversity of research approaches have been used to study mango fruit health benefits, and those can be grouped into three main categories: a) those that present the associations or direct effects of the edible portion of the fruit on health through observational epidemiological studies and clinical trials; b) in vivo and in vitro experimental approaches that address either the physiological effects or mechanisms of several kinds of extracts or purified components of mango fruit (pulp, peel and seed), and c) preclinical and clinical studies that explore the possible pharmacological uses of mango fruit. Current scientific understanding of mango health benefits suggest that consumption of mango fruit and its byproducts containing bioactive components can be useful as part of a healthy diet in order to reduce the incidence of health problems.